Teacher Involvement in Parent Collaboration to Foster Social–Emotional Maturity of Early Childhood Group A Learners - Nur Inayah; Agustien Lilawati; Mush'ab Al Umairi (Al-Qalam Institue, 2025)
Social–emotional maturity in early childhood is shaped through interactions across home and school. This study aims to examine how teachers and parents collaboratively support social–emotional development through structured communication and reinforcement. Using a qualitative descriptive design, data were collected from teachers, parents, and school leaders through interviews, observations of classroom behaviors, and analysis of communication documents. The findings show that teachers strategically initiate collaborative structures, consistent reinforcement between home and school strengthens children’s emotional regulation shown by 82% success in routine-following and 76% non-aggressive conflict resolution and communication barriers reduce the continuity of collaborative developmental support. The study contributes a model positioning teachers as drivers of collaboration, rather than passive partners, in emotional development. The practical implication suggests that schools need systematic and reciprocal communication cycles to sustain parental engagement and prevent fragmented reinforcement of emotional competencies.